City residents’ awareness and perception of covid 19 vaccination - Adedoyin Oluwatosin Esan; Juliana Afebanye Ushie (Record and Library Journal, 2022)
Background of the study: With the roll out of vaccines in Edo state and the increasing number of cases of infections, it has become imperative to investigate residents’ awareness and perception of the Corona virus vaccine in order to understand the willingness and readiness of the public to accept vaccines in Benin City. Purpose: The study investigates Benin City residents’ awareness and perception of COVID19 vaccination. Method: A descriptive survey was adopted for the research. The study setting is the Benin metropolis. A sample of 400 respondents was drawn randomly from the resident population for the research from three local government areas that make up the Benin metropolis. Findings: The study found that social media is the most important source of awareness on COVID 19 vaccination, the perception of COVID 19 vaccination is poor among Benin city residents, the willingness to participate in the COVID19 vaccination is poor and factors affecting COVID19 vaccinations among Benin city residents are the systems factors of government and the healthcare system and personal doubts about vaccinations Conclusion: It is evident that the poor perception is a stumbling block to the acceptance of the COVID 19 vaccines and may derive attempts to reach herd immunity in Benin City.